Addressing Health Literacy in Patient Decision Aids: An Update from the International Patient Decision Aid Standards. (October 2021) - Muscat, Danielle M.; Smith, Jenna; Mac, Olivia; Cadet, Tamara; Giguere, Anik; Housten, Ashley J.; Langford, Aisha T.; Smith, Sian K.; Durand, Marie-Anne; McCaffery, Kirsten
Background: There is increasing recognition of the importance of addressing health literacy in patient decision aid (PtDA) development. Purpose: An updated review as part of IPDAS 2.0 examined the extent to which PtDAs are designed to meet the needs of people with low health literacy/socially-disadvantaged populations. Data Sources: Reference lists of Cochrane reviews of randomized controlled trials (RCTs) of PtDAs (2014, 2017, and upcoming 2021 versions). Study Selection: RCTs that assessed the impact of PtDAs on low health literacy or other socially-disadvantaged groups (i.e., ≥50% participants from socially-disadvantaged groups and/or subgroup analysis in socially-disadvantaged group/s). Data Extraction: Two researchers independently extracted data into a standardized form including PtDA development and evaluation details. We searched online repositories and emailed authors to access PtDAs to verify grade reading level, understandability, and actionability. Data Synthesis: Twenty-five of 213 RCTs met the inclusion criteria, illustrating that only 12% of studies addressed the needs of low health literacy or other socially-disadvantaged groups. Grade reading level was calculated in 8 of 25 studies (33%), which is recommended in previous IPDAS guidelines. We accessed and independently assessed 11 PtDAs. None were written at sixth-grade level or below. Ten PtDAs met the recommended threshold for understandability, but only 5 met the recommended threshold for actionability. We also conducted a post hoc subgroup meta-analysis and found that knowledge improvements after receiving a PtDA were greater in studies that reported using strategies to reduce cognitive demand in PtDA development compared with studies that did not (χ 2 = 14.11, P = 0.0002, I 2 = 92.9%). Limitations: We were unable to access 13 of 24 PtDAs.Conclusions. Greater attention to health literacy and socially-disadvantaged populations is needed in the field of PtDAs to ensure equity in decision support.